????? ???????? ?????? ???????? ????????? ?????? "??? ???????" ?????????? ????????? ????????? - Majidatun Ahmala (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2017)
The strategy used by the teacher is the teacher’s efforts to make learning activities more active and effective. Therefore, a pictorial conversation strategy is chosen to make the learning activities can be planned in detail by utilizing the experience, stimuli and senses of students who are able to bring the student’s imagination to the new vocabulary they have learned. Thus, this strategy can be a means for teachers and students to expand all innovation, creativity and freedom of expression of the forms of conversation that students want to give the new vocabulary to be learned. This study uses the Classroom Action Research method with the following steps; (1) Observation; (2) design of teaching plans; (3) implementation; (4) supervision; (5) reflection; (6) evaluation. This research was conducted in Nurul Islam elementary school in Sukodono-Sidoarjo, East Java. The purpose of this study is, (1) to uncover the pictorial conversation strategy in solving problems of students who have difficulty in remembering the vocabulary that has been learned; (2) fostering interest in reading and speaking in Arabic, because this strategy is equipped with images that will attract student’s attention, and (3) knowing how effective this strategy can be used in the world of education, especially in the process of learning Arabic.